2022
DOI: 10.21037/atm-22-4319
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a predictive model for in-hospital mortality in patients with sepsis-associated liver injury

Abstract: Background: Sepsis is often accompanied by organ dysfunction and acute organ failure, among which the liver is commonly involved. Sepsis patients suffering from liver injury have a greater risk of mortality than patients suffering from general sepsis. As of now, there are no tools that are specifically designed for assessing the prognosis of such patients. This study aimed to develop and validate a model to predict the risk of inhospital mortality in patients with sepsis-associated liver injury (SALI).Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 41 publications
(52 reference statements)
1
14
0
Order By: Relevance
“…The results of our research reported a morbidity rate of 7.91% (1039 of 12129 patients) and mortality rate of 44.10% (458 of 1039 patients) in patients with SALI, suggesting a lower incidence and higher death rate than the Liu Y et al 15 and Kobashi et al 26 clinical reports. We found that Liu Y's team used the older data version 1.0 of MIMIC-IV, which only included liver function indicators in the SALI diagnostic criteria and did not include the more novel combined liver function and coagulation criteria, while that allowed the inclusion of SALI diagnosed any time within 48 hours of hospitalization, but our study only included the rst 24 hours of ICU MIMIC-IV in version 2.0.…”
Section: Discussionmentioning
confidence: 43%
See 4 more Smart Citations
“…The results of our research reported a morbidity rate of 7.91% (1039 of 12129 patients) and mortality rate of 44.10% (458 of 1039 patients) in patients with SALI, suggesting a lower incidence and higher death rate than the Liu Y et al 15 and Kobashi et al 26 clinical reports. We found that Liu Y's team used the older data version 1.0 of MIMIC-IV, which only included liver function indicators in the SALI diagnostic criteria and did not include the more novel combined liver function and coagulation criteria, while that allowed the inclusion of SALI diagnosed any time within 48 hours of hospitalization, but our study only included the rst 24 hours of ICU MIMIC-IV in version 2.0.…”
Section: Discussionmentioning
confidence: 43%
“…Additionally, among subjects who were at or over 40 years of age, these percentages were 51.5%, 15.9%, and 32.6%, respectively 26 . In a recent study, a scholar referred to age as an important component of mortality involved in SALI patients 15 . With the increasing severity of sepsis disease, a large proportion of patients have circulatory instability and require ascending agents to maintain hemodynamic stability [36][37][38] , yet the inclusion of vasopressors and mean arterial pressure were rst reported in sepsisassociated liver injury in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations